Tyrphostin AG490 reduces inflammation and fibrosis in neonatal obstructive nephropathy - Gasparitsch, Mojca; Schieber, Alexandra; Schaubeck, Teresa; Keller, Ursula; Cattaruzza, Marco; Lange-Sperandio, Bärbel (PLOS ONE, 2019)
Background: Congenital obstructive nephropathy is the main cause of end-stage renal disease in infants and children. Renal insufficiency is due to impaired growth and maturation in the developing kidney with obstruction. Congenital obstructive nephropathy leads to cytokine mediated inflammation and the development of interstitial fibrosis. The Janus kinase-2 (JAK-2) and Signal Transducer and Activator of Transcription’-3 (STAT3) are involved in cytokine production, inflammation, and interstitial fibrosis. Methods We studied the role of JAK2/STAT3 in a model of congenital obstructive nephropathy using unilateral ureteral obstruction (UUO) in neonatal mice at the second day of life. Cytokine production, inflammation, and interstitial fibrosis were analyzed in obstructed and sham operated kidneys of neonatal mice treated with or without JAK2/STAT3 inhibitor Tyrphostin AG490. To mimic obstruction and distension, proximal tubular cells were stretched in vitro. Results We show that STAT3 is highly activated in the developing kidney with obstruction and in proximal tubular cells following stretch. JAK2/STAT3 activation mediates cytokine release and leukocyte recruitment into neonatal kidneys after UUO. Pharmacological blockade of JAK2/STAT3 by Tyrphostin AG490 reduced inflammation, tubular apoptosis, and interstitial fibrosis. JAK2/STAT3 blockade decreased pro-inflammatory and profibrotic mediators in tubular cells. Conclusion Our findings provide evidence that JAK2/STAT3 mediates inflammation and fibrosis in the developing kidney with obstruction. Blocking JAK2/STAT3 may prove beneficial in congenital obstructive nephropathy in children.